Competencies for food graduate careers: developing a language tool - Weston, Emma; Crilly, Jim; Mossop, Liz; Foster, Tim (Taylor & Francis, 2017)
Unlike many other graduate career pathways in the UK, the food industry does not have a cohesive competency framework to support employers, students and degree providers. Food sciences-based technical graduates are a significant proportion of the industry’s graduate intake; this study aims to provide such a framework. Initial work involving a sample of representative stakeholders has created a list of typical attributes and associated definitions that may be desirable in food sciences graduates. Material was gathered by semi-structured qualitative interviews and analysed by thematic analysis followed by a modified Delphi technique. The resulting framework is tailored to needs and terminology prevalent in food industry employment. The process employed could be utilised for building other vocational graduate competency frameworks. Further plans include using the framework to ascertain the important elements for typical graduate entry roles, better informing students about desirable qualities and supporting future competency-based curriculum review.